2010
DOI: 10.1053/j.gastro.2010.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of Calcineurin 1 Controls Growth Plasticity of Adult Pancreas

Abstract: Background & Aims-Growth of exocrine pancreas is regulated by GI hormones, notably cholecystokinin (CCK). CCK-driven pancreatic growth requires calcineurin (CN), which activates NFATs (Nuclear Factor of Activated T-cells), but the genetic underpinnings and feedback mechanisms that regulate this response are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…The 38 genes included feedback inhibitors (Rcan1, Socs3, Rgs2, Socs 2, Lif), growth factors (FGF21, HBEGF) and transcriptional regulators. About 60% had predicted NFAT regulation and CHIP analysis confirmed this for 5 genes in pancreatic 266-6 acinar cells stimulated with calcium ionophore (48). …”
Section: Calcineurin-nfat Pathwaymentioning
confidence: 67%
See 1 more Smart Citation
“…The 38 genes included feedback inhibitors (Rcan1, Socs3, Rgs2, Socs 2, Lif), growth factors (FGF21, HBEGF) and transcriptional regulators. About 60% had predicted NFAT regulation and CHIP analysis confirmed this for 5 genes in pancreatic 266-6 acinar cells stimulated with calcium ionophore (48). …”
Section: Calcineurin-nfat Pathwaymentioning
confidence: 67%
“…RNA microarray analysis of pancreatic genes revealed 38 genes induced by TI two hours after feeding that were at least 70% inhibited by FK-506 (48). These changes were not observed in CCK deficient mice.…”
Section: Calcineurin-nfat Pathwaymentioning
confidence: 95%
“…Despite their differences in size, the two are almost equally potent inhibitors of CN (29). Rcan1.4, however, contains tandem NFAT binding sites in its promoter and as shown both in our work (14) and multiple other studies (38,40), its product is the only one among Rcan1 variants whose expression is regulated by CN-NFAT signaling. The alternative Rcan1.1 variant also inhibits calcineurin but is regulated by Notch/Hes1 and oxidative stress (25,33).…”
Section: Gene/protein Structure and Intracellular Functionmentioning
confidence: 72%
“…In our past work, we had shown that Rcan1 is the only member of the RCAN family to be induced in response to CCK in the course of pancreatic growth (14). We also detailed its role as a feedback inhibitor of CN-NFAT signaling and established the CN-NFAT-Rcan1 axis as the first molecular switch or negative feedback regulator of adaptive, hormonally-regulated pancreatic growth (14).…”
Section: Rcan1 Function In the Pancreasmentioning
confidence: 99%
See 1 more Smart Citation